GMR-Hungary: A Complex Macro-Regional Model for the Analysis of Development Policy Impacts on the Hungarian Economy - Varga, Attila (PTE KTK Műhelytanulmányok, 2022)
The National Development Office of the Hungarian government contracted the international consortium coordinated by the Center for Research in Economic Policy for the development of a complex macro-regional economic model. This model system will be used for ex-ante evaluations of different policy scenarios according to the following specifications: 1. The model is the extension of EcoRET – a macroeconomic model used for ex-ante impact analyses during the design of the 1st National Development Plan for Hungary – into the regional and the sectoral directions. For the regional extension EcoRET ...